KENAKALAN REMAJA DALAM PROYEKSI PENEGAKAN HUKUM - Alfanda Refandiasworo; Edy Soesanto, Muhamad Fadillah, Rama Sigit Nugraha (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This study focuses on optimizing law enforcement against juvenile crimes in order to reduce the number of criminal acts that commonly occur in Indonesia. Law enforcement is the process of realizing the hopes and desires of the law so that they become a reality to be implemented and respected by society. Teenagers are the country's future assets, in fact currently more and more crimes are being committed by teenagers, such as drug abuse and street crime in the form of gangsters. This problem is no longer strange nowadays. Juvenile crime is an act or conduct that is contrary to the provisions of the criminal law committed by teenagers individually or collectively. It is necessary to pay attention to the many internal and external factors that cause juvenile delinquency. To overcome this, parental supervision and a good environment can determine adolescent growth and development. This research was carried out with the aim of conducting a literature review regarding the meaning of juvenile delinquency, the factors that cause juvenile delinquency, and how law enforcement deals with juvenile delinquency. This type of research uses a qualitative approach with a literature review method, searches are carried out in the Google Schoolar electronic database. Based on the results of observations made by the author in schools in Bekasi City, currently there are still many forms of non-formal social groups emerging which are thought to be a link in the chain of the free life of teenagers who are commonly called "gangsters" or "gangs". Adolescence, most of whom have the social status of students, especially students at the upper secondary level and above, is the most unstable period because at that age teenagers are most vulnerable to participating in student associations which lead to negative actions. The conclusion regarding law enforcement against juvenile delinquency is that this is an important aspect in maintaining public order and security.